Perjanjian pranikah dalam perspektif Islam: Apakah kafaah sudah diatur sebelumnya? - Amelia, Fuji Nur Rizqi (Maliki Interdisciplinary Journal, 2025)
Prenuptial agreements are increasingly becoming a significant topic in the realm of legal matters and the protection of spousal rights in Indonesia, especially within the predominantly Muslim community. This article explores the connection between prenuptial agreements in positive law and the concept of kafaah in Islam, which has long served as the foundation for equality and compatibility prior to marriage. Kafaah encompasses religious, lineage, social, and moral dimensions aimed at preserving familial harmony, even though it is not formally documented. A prenuptial agreement, which outlines the division of assets and the rights of each partner in writing, has a similar aim of preventing disputes and safeguarding the rights of both parties. From an Islamic jurisprudence perspective, prenuptial agreements are permissible as long as they do not conflict with the principles of Sharia and are founded on fairness and the mutual consent of both individuals. Thus, a prenuptial agreement can be regarded as a tangible representation of kafaah values within modern legal frameworks. The article concludes that Islam and positive law can complement each other in fostering a harmonious and equitable household. Recommendations are aimed at prospective couples to grasp the concept of kafaah and utilize prenuptial agreements, at religious institutions to educate partners, and at the government to enhance regulations and awareness to ensure prenuptial agreements are widely accepted within the Muslim community.